Reduced TCA Flux in Diabetic Myotubes: Determined by Single Defects? - Michael Gaster (Biochemistry Research International)
The diabetic phenotype is complex, requiring elucidation of key initiating defects. Diabetic myotubes express a primary reduced tricarboxylic acid (TCA) cycle flux but at present it is unclear in which part of the TCA cycle the defect is localised. In order to localise the defect we studied ATP production in isolated mitochondria from substrates entering the TCA cycle at various points. ATP production was measured by luminescence with or without concomitant ATP utilisation by hexokinase in mitochondria isolated from myotubes established from eight lean and eight type 2 diabetic subjects. The ATP production of investigated substrate combinations was significantly reduced in mitochondria isolated from type 2 diabetic subjects compared to lean. However, when ATP synthesis rates at different substrate combinations were normalized to the corresponding individual pyruvate-malate rate, there was no significant difference between groups. These results show that the primary reduced TCA cycle flux in diabetic myotubes is not explained by defects in specific part of the TCA cycle but rather results from a general downregulation of the TCA cycle.